Determination of aerodynamic properties of javelin by means of computational fluid dynamics - González-Martinez, A.; Martinez-Rodriguez, A.; Laffita-Leyva, A. (Revista Internacional de Ciencias del Deporte, 2019)
During the flight of the javelin its interaction with the surrounding air presents a relevant importance, which is characterized by the coefficients of lift and drag and by the position of the center of pressures. Usually these parameters are determined in wind tunnels with the required span to accommodate an implement of these dimensions, being difficult to avoid interferences of the support means, as well as achieving the experimental measurement of the fields of pressures and velocities in the vicinity of the javelin. To solve these difficulties, in the present work the computerized simulation of the javelin-air interaction using Computational Fluid Dynamics (CFD) tools is carried out. Three-dimensional models of javelins with official weight and dimensions, were subjected to an air stream, with five levels of relative speed between the air and the javelin and eight levels of attack angle. As a result, the adjustment curves of the drag and lift coefficients vs. the angle of attack for both types of javelin were obtained. Likewise, the position of the center of pressures and the magnitude and direction of the pitching moment as a function of the relative velocity between the air and the javelin (masculine modality) for different angles of attack were determined. The results obtained are of relevant importance for the development of mathematical models of simulation of the javelin flight, which can be used by coaches and athletes with a view to improving the release parameters in order to obtain better performance.